Metabolomic profiling for identification of metabolites and relevant pathways for taurine in hepatic stellate cells - Deng, Xin (World J Gastroenterol, 2017)
AIM: To develop a reliable and simple method to identify important biological metabolites and relevant pathways for taurine in hepatic stellate cells (HSCs), in order to provide more data for taurine therapy. METHODS: All the biological samples were analyzed by using high-performance liquid chromatography-time electrospray ionization/quadrupole-time of flight mass spectrometry. Principal component analysis and partial least squares discriminant analysis were used to identify statistically different metabolites for taurine in HSCs, and metabolomic pathway analysis was used to do pathway analysis for taurine in HSCs. The chemical structure of the related metabolites and pathways was identified by comparing the m/z ratio and ion mode with the data obtained from free online databases. RESULTS: A total of 32 signiﬁcant differential endogenous metabolites were identified, which may be related to the mechanism of action of taurine in HSCs. Among the seven relevant pathways identified, sphingolipid metabolism pathway, glutathione metabolism pathway and thiamine metabolism pathway were found to be the most important metabolic pathways for taurine in HSCs. CONCLUSION: This study showed that there were distinct changes in biological metabolites of taurine in HSCs and three differential metabolic pathways including sphingolipid pathway, glutathione pathway and thiamine metabolism pathway might be of key importance in mediating the mechanism of action of taurine in HSCs.